Striking poses: The fantastic figure of Yul Brynner - Paasonen Susanna (My University, 2025)
Since his successful 1956 appearances in the Hollywood films The King and 1 (Walter Lang),
Ten Commandments (Cecil B. DeMille) and Anastasia (Anatole Litvak), Yul Brynner’s star
image emerged as elaborately masculine, foreign and exotic, as well as markedly flexible in
the range of ethnicities that it was set to convey. Combined with his varying mythical tales of
international origins and sexual prowess, Brynner’s intense gestural register and striking body
aesthetic, as encapsulated in the trademark baldness, rendered the actor a spectacular sight in
1950s Hollywood. In fact Brynner’s mere physical presence dominates many of his films in
ways suggestive of elasticity between acting and presence, role and actor – as well as of the
centrality of screen presence more generally. This article explores Brynner’s fantastic
cinematic figure image in terms of its fabrication, flexibility and reappearance by examining
both his film work and biographical accounts. It tracks transformations and continuities in
Brynner’s performance style with specific attention on its idiosyncratic and repetitive
elements in terms of pose, gesture and motion, with the aim of foregrounding the role of
physicality – both material and represented – in the creation of star image.